Accelerating Sharia Fintech Based on a Green Economy: The Creative Role of the Young Generation in the Society 5.0 Era - Aniesatun Nurul Aliefah (al-Afkar, Journal For Islamic Studies, 2026)
This research explores the role of the younger generation in optimizing sharia fintech through digital economy creativity and green economy in the Society 5.0 era for sustainable Islamic economic growth. Using qualitative research methods, this study analyzes how digital technologies, particularly Islamic fintech, contribute to financial inclusion and environmental sustainability. This study uses data from in-depth interviews and case studies to understand the perspective of the younger generation on the use of sharia fintech and its impact on the green economy. The results of the study show that the young generation has great potential in advancing sharia fintech, especially through innovations that support environmental sustainability and sharia principles. The findings also reveal that sharia fintech can meet Islamic financial criteria and contribute to financial inclusion. The implications of this study show the need for policies that support the development of sharia fintech and education that focuses on digital innovation. The recommendations for stakeholders including policymakers, academics, and practitioners of the sharia fintech industry are to strengthen support for the younger generation, create regulations that support innovation, and develop an environmentally friendly fintech platform.